Pengaruh Digital Marketing, Kualitas Layanan dan Brand Image terhadap Keunggulan Bersaing pada Showroom Astra Daihatsu Medan Krakatau - Anggreini Laowo; Elisabeth Nainggolan; Lisa Elianti Nasution (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the influence of digital marketing, service quality, and brand image on competitive advantage at the Astra Daihatsu Medan Krakatau Showroom. The study employs a quantitative approach using a survey method, involving the distribution of questionnaires to showroom customers. The sampling technique utilized purposive sampling to obtain a sufficient number of respondents who met the study’s criteria. The data obtained were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that digital marketing and service quality have a significant impact on competitive advantage; however, they have not yet been able to provide an optimal contribution to enhancing the company’s competitiveness. Meanwhile, brand image has a positive and significant influence and is the most dominant factor in shaping competitive advantage. This indicates that a strong brand image can enhance consumer trust and positive perceptions of the company. Simultaneously, digital marketing, service quality, and brand image significantly influence the competitive advantage of the showroom. Therefore, the company needs to enhance the effectiveness of its digital marketing strategies, improve service quality, and continuously strengthen its brand image to boost the company’s competitiveness amid the increasingly competitive automotive industry